Effect of immunostimulating Limosilactobacillus strain in rats with trinitrobenzenesulfonate (TNBS)-induced colitis - Lukić, Jovanka; Strahinić, Ivana; Milenković, Marina; Begović, Jelena (Archives of Pharmacy, 2023)
The aim of the study was to test the potential of immunostimulating Limosilactobacillus fermentum BGHI14 strain to reduce the damage of colon tissue in rats with 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis. Wistar rats were treated with L. fermentum BGHI14 in the regime of preventive, therapeutic and continuous treatment 22 days prior to and/or 7 days after the administration of TNBS. After sacrifice, the colon tissue samples were taken for RNA isolation, gene expression analysis, histopathological analysis, and malondialdehyde measurement. Judging from the body weights, histopathological scores, malondialdehyde levels and transcription of IL-1β and Tight junction protein 1 (Tjp-1) coding genes, preventive and therapeutic treatment proved to be the most protective in the applied conditions. On the other hand, continuous treatment did not affect the intensity of tissue damage. Considering these results, we discussed the possible mechanisms which might stand behind the protective action of immunostimulating probiotic bacteria in the case of mucosal barrier damage.